2019
DOI: 10.1002/ppap.201970024
|View full text |Cite
|
Sign up to set email alerts
|

Inside Cover Picture: Plasma Process. Polym. 11/2019

Abstract: Inside Front Cover: We establish a theoretical ground for capacitively coupled plasma (CCP) considering ion‐induced secondary electron emission (SEE) under low pressure. Plasma parameters are derived from kinetic theory including density, potential, sheath capacitance, power balance etc. Space potential is determined as a sum of time‐averaged component and oscillating component. The former is determined by emission coeffi cient and applied voltage, while the latter has limited relevance with SEE. A numerical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Electron-induced secondary electron emission (ESEE) on the dielectric, ion-induced secondary electron emission (ISEE) on the metallic electrode, metal sputtering due to incident ions, ionization/electron-neutral collisions, outgassing and the relativistic effects of fast electrons are included in the simulation with similar algorithms in previous studies [17,18,43]. The data for the collision cross-section are imported from an existing database similar to our related works on plasma simulation [49,50]. A schematic of the simulation code is given in figure 1(d).…”
Section: Methodsmentioning
confidence: 99%
“…Electron-induced secondary electron emission (ESEE) on the dielectric, ion-induced secondary electron emission (ISEE) on the metallic electrode, metal sputtering due to incident ions, ionization/electron-neutral collisions, outgassing and the relativistic effects of fast electrons are included in the simulation with similar algorithms in previous studies [17,18,43]. The data for the collision cross-section are imported from an existing database similar to our related works on plasma simulation [49,50]. A schematic of the simulation code is given in figure 1(d).…”
Section: Methodsmentioning
confidence: 99%
“…Approaches like this are very convenient in simulation code to determine sheath edge location [12]. A similar criterion also using the non-neutrality sets the sheath edge at the location where (n i − n e )/n i = δ [10,62,63]. In theoretical analyses, the oscillating 'step function' electron density profile is commonly used [44,64,65].…”
Section: Simulation Resultsmentioning
confidence: 99%
“…In previous works, it has been confirmed experimentally that the secondary electron emission (SEE) can significantly modify important plasma parameters, such as the temperature, density, and particle/power balance [5,6]. Previous theoretical studies indicate that the SEE significantly modifies the plasma discharge characteristics [8,9]; these works also express the RF sheath as a function of the source amplitude and the SEE coefficient, giving quantitative current-voltage characteristic, sheath capacitance and conductance in the presence of boundary electron emission [10,11]. In addition to experimental and theoretical approaches, numerical simulations provide further insight into the physical details of PSI in CCP discharges.…”
Section: Introductionmentioning
confidence: 93%
“…In earlier studies of ion-induced secondary electron (γ-electron) emission, a constant emission coefficient was usually set in the simulations due to a lack of data for the energyand material-dependent surface coefficients. Despite this, such studies reported strong effects of the γ-electron emission coefficients (the γ-coefficient) on the discharge operation mode [63][64][65][66][67][68]. When a low γ-coefficient was used in the simulations of argon discharges, the discharge was usually found to operate in the α-mode [69].…”
Section: Introductionmentioning
confidence: 99%